كشف القرآن الأساليب التحريف في التوراة والإنجيل : دراسة تحليلية نقدية - بالله، محمد معصوم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study basically aims at highlighting the ways used by Jewish rabbis and Christian monks in distorting the divine Torah and Gospel respectively in the light of Qur'anic verses that deal with those manners of distortion. The methods used in this study are inductive and analytical whereby the researcher collected the data concerning the distortion of the Torah and Gospel from the classical and contemporary books of Qur'anic interpretation, other books and on-line sources related to the study. After the data collection, the researcher followed the analytical method to establish the evidence on the ways of distortion. It is followed by a critique of Jewish and Christian tactics in distortion. The most important findings of this study are: (1) twenty verses of the Holy Qur'an have disclosed the ways applied by the Jews and Christians in their distortion activities; (2) fifteen verses point out to the motives which led the rabbis and monks to distortion; and (3) twenty five verses refer to the places in the previous Scriptures where the distortion has occurred. This study has identified 11 ways of distortion in the Biblical texts: (1) attributing human works to the words of Allah SWT; (2) hiding a number of revealed texts; (3) mixing up the truth with falsehood; (4) mispronouncing the sacred texts; (5) pushing to oblivion a great portion of the Biblical texts memorized by rabbis and monks; (6) following only those favourable rules of Torah and Gospel and rejecting unfavourable ones; (7) telling lies and accusing others of speaking lies; (8) suspending practical relevance of revelation; (9) believing in some verses of the divine book and rejecting some others; (10) ignoring the divine texts; and (11) making speculations.